Improving Quality Education Based on Quality Management and Character Based Education - Rivauzi, Ahmad (Universitas Negeri Padang, 2023)
This paper describes how to improve the quality of education. This research is library research, analyzed qualitatively because there is an interest in interpretation and seeking meaning from written texts in literary sources. Schools must play a role in helping students learn about values so that they know and can understand good values, schools must stimulate and foster students' moral awareness so that they have an awareness of values, and schools must also provide space, assistance, and supervision to students to do and work on good values. Quality management and organizational commitment are very important related to the quality of education. In the Quran, the word commitment corresponds to the word إعتصام which can be found 14 times in repetition in several verses and letters and can be interpreted as maintaining, protecting, or holding fast (istamsaka). Management is synonymous with the word